International and regional cooperation in disaster management - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Robert Czerski (Kazimierz Wielki University, 2018)
Every year in the world there happens about 150 different types of disasters. Natural disasters that accompanied the Earth since the dawn of history cannot be predicted. International assistance and cooperation in case of disaster is the result of experiences that humanity has gained as a result of the dramatic events following the mass. The study characterized the main entities involved in international aid for disasters as well characterized procedures taken in case of such events.